Research status and warming of the risk of earth subsidence-cracking in the Tay Nguyen area - Hùng, Phạm Văn; Huyên, Nguyễn Xuân (Vietnam Journal of Earth Sciences, 2014)
On the basis of assessment of the status and cause analysis has allowed assessment of the risk of earth subsidence-cracking in the Tay Nguyen area.In the Tay Nguyen area occur 91 points of earth subsidence-cracking, including 21 points large losses danger to the lives of local residents. The distribution of earth subsidence-cracking in the sub-bands have the meridian in the north and south of NE-SW in the Tay Nguyen area. The bands have the meridian, such as: Dak Glei-Ngoc Hoi-Duc Co, Tu MoRong-Dak To-Kon Tum, Xa Hieu-Kbang-An Khe. The range is the NE-SW: Ea Ka-Dak Mil-Tuy Duc, M’Drak-Lak-Cat Tien, Don Duong-Di Linh. Also in the Tay Nguyen area distributed earth subsidence -cracking in NW-SE: Yaly-Pleiku- Ayun Pa-Krong Pa.Earth subsidence-cracking hazard in the Tay Nguyen area is arising under the action of the elements of tectonic and geology. To this emerging are new elements of neotectonic movement, fault density, fault zone dynamics activities, geological characteristics of the lithology and hydrogeology.On the Tay Nguyen area is the risk of moderate earth subsidence-cracking. Areas with very high and high risk of earth subsidence-cracking are distributed a wide range of 7-10km: Dak Glei-Duc Co, Xa Hieu -Kbang-An Khe, Chu Pah-Ayun Pa-Krong Pa, M’Drak-Krong Bong-Dak Glong-Cat Tien, Dak Song-Dak Rlap, Don Duong-Duc Trong-Di Linh. Areasat risk of average earth subsidence-cracking are widely distributed east of Kon Tum, Gia Lai province to the west and north of Dak Lak. Areas at risk of low and very low earth subsidence-cracking are widely distributed in the western of Dak Lak province, south of Lam Dong province.